Socioeconomic position and mortality among patients with prostate cancer: influence of mediating factors. (3rd April 2017) - Larsen, Signe Benzon; Brasso, Klaus; Christensen, Jane; Johansen, Christoffer; Tjønneland, Anne; Friis, Søren; Iversen, Peter; Dalton, Susanne Oksbjerg
Abstract: Introduction: Men with low socioeconomic position experience higher mortality after a prostate cancer diagnosis compared to men with a higher socioeconomic position, however, the specific mediators of this association are unclear. We therefore evaluated the influence of potential mediators on the association between socioeconomic position, and prostate cancer-specific and all-cause death in prostate cancer patients. Materials and methods: We conducted a cohort study of prostate cancer patients in the Danish Diet, Cancer and Health study. All patients completed questionnaires and anthropometric measurements at enrollment. Information on educational level, income, comorbidity and vital status was obtained by linkage to Danish nationwide registries. Clinical data and anthropometric measures were collected from medical records at diagnosis. Cox proportional hazard models were used to compute hazard ratios (HR) for all-cause and prostate cancer-specific death according to socioeconomic position and potential mediators. Results: We included 953 prostate cancer patients identified among 27 179 male participants in the Diet, Cancer and Health study who were followed for a median of 6.5 years (interquartile range 6.4–11.2 years). Patients with low socioeconomic position were more often overweight or obese at baseline. Low socioeconomic position was associated with increased prostate cancer-specific and all-cause death. The increased mortality could largely be explained by tumor aggressiveness, comorbidity, treatment and metabolic indicators, except for patients in the lowest income group. Discussion: Our study confirmed the a priori assumption that socioeconomic position is associated with increased mortality after prostate cancer. The increased mortality could largely be explained by lifestyle and clinical parameters.